Greatly enhanced electronic conduction and lithium storage of faceted TiO2 crystals supported on metallic substrates by tuning crystallographic orientation of TiO2 - Liu, G.; Yin, L.; Pan, Jian; Li, F.; Wen, L.; Zhen, C.; Cheng, H. (Wiley - V C H Verlag GmbH & Co. KGaA, 2015)
Electronic conduction along the [001] direction of a faceted anatase TiO2 particle in contact with two tungsten probes is found to be an order of magnitude higher than that along the [010] direction due to a smaller potential barrier of the TiO2(001)–tungsten interface for electron transport than the TiO2(010)–tungsten interface. This finding could guide the design of TiO2-based electrodes.